Inequidad salarial en Cuba durante el período especial. - Galbraith, James K.; Munevar, Daniel; Spagnolo, Laura (Salamanca ES: Ediciones Universidad de Salamanca)
Realidad Nacional y su Contexto
Keywords: EQUIDAD ECONOMICA; SALARIOS; ECONOMIA; SOCIEDAD; REVOLUCION; CUBA#El